2019
DOI: 10.4103/ajns.ajns_149_19
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of trigger finger following carpal tunnel release

Abstract: Surgical treatment of carpal tunnel syndrome (CTS) was recently started in our department, and we noticed that the development of trigger finger (TF), with which neurosurgeons are generally unfamiliar, is not rare after such treatment. We summarized the clinical and pathogenetic aspects of TF and retrospectively analyzed the medical records of all 39 patients who underwent CTR in our department to investigate the occurrence of TF. In 39 patients with CTS, 46 surgical interventions were performed in our departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…sliding of the flexor tendons in the inner lining. 13 A similar process develops in de Quervain's disease. Thickening of the tendon sheath due to mucopolysaccharide deposition and myxoid degeneration corresponding to chronic TLL-tumor-like lesions (1 Ganglioma, 2 benign giant-cell tumors of tendon sheet), CTS -carpal tunnel syndrome degenerative changes, rather than an inflammatory reaction, was demonstrated in a study conducted in England by examining histopathological specimens taken from 23 operatively treated patients with de Quervain's disease.…”
Section: Discussionmentioning
confidence: 84%
“…sliding of the flexor tendons in the inner lining. 13 A similar process develops in de Quervain's disease. Thickening of the tendon sheath due to mucopolysaccharide deposition and myxoid degeneration corresponding to chronic TLL-tumor-like lesions (1 Ganglioma, 2 benign giant-cell tumors of tendon sheet), CTS -carpal tunnel syndrome degenerative changes, rather than an inflammatory reaction, was demonstrated in a study conducted in England by examining histopathological specimens taken from 23 operatively treated patients with de Quervain's disease.…”
Section: Discussionmentioning
confidence: 84%
“…The literature indicates that trigger finger may occur in combination with carpal tunnel surgery and that these two diagnoses are frequently seen in the same patient. 38 39 40 41 El-Hadidi et al 42 offered an explanation for the association between carpal tunnel surgery and trigger finger; he described that the angle between the A1 pulley and the flexor tendon increases during carpal tunnel surgery, and this could precipitate greater friction between these two and potentially lead to the onset of a trigger digit. In addition, patients older than 65 were more likely to have a successful outcome after the first injection.…”
Section: Discussionmentioning
confidence: 99%
“…Yunoki et al [15] reported on 39 patients who underwent 46 open carpal tunnel release procedures. After carpal tunnel release, trigger finger occurred in 9 hands of 8 patients.…”
Section: Discussionmentioning
confidence: 99%